Improving water security to mediate impacts of climate change in the Ganges Basin - Sharma, Bharat; Pavelic, Paul; Amarasinghe, Upali (Springer, 2021)
In spite of being water surplus, the 600+ million population of the large Ganges basin spread over 1.09 m km2 in South Asia is water insecure, poor, and highly exposed to water-induced stresses of floods and droughts. The contribution from the glaciers to the streamflow is ~70% in the Himalayan catchments though spatially distributed quantification is unavailable. An application of the Water Evaluation and Planning (WEAP) model with a sub-routine for snow and glaciers melt processes in the basin was set up. The model also examined the possible impacts of an increase in temperature of +1, +2 or +3°C over 20 yrs of the simulation period. The impact on stream flows was high in the upstream (+8 to +26% at Tehri Dam) and moderate in downstream (+1 to +4% at Farakka). These increases shall create flood events more frequently or of higher magnitude in the mountains and Upper Ganga flood plains. To moderate the climate-change induced impacts of floods and improve water security during the non-monsoon season the novel concepts of Underground Taming of Floods for Irrigation (UTFI) and Cranking up the Ganges Water Machine for Ecosystem Services (GAMES) were developed, and pilot tested in the Ramganga sub-basin. Analysis showed that there is an assured possibility of reducing the floods and enhancing sub-surface storage in the identified basins to the level of 45 Bm3. The demonstrated managed aquifer recharge interventions are technically feasible, operationally acceptable and economically viable.